Applying behavioral Management Strategies to Children Parental Counseling: Array - Mihai, Alexandra (New Trends in Psychology, 2020)
According to Mash and Terdal (1996), the purpose of any behavioral assessment and intervention must be very clearly defined, ie to be relevant to the allegations made by the child and his family, to be relevant to the child’s current and future adaptation, to be based on a appropriate theory of developing and maintaining adaptation. The main target of this intervention program, the noncompliant and difficult child, certainly meets these requirements (Forehand and McMahon, 1981). The child’s behavior does not correspond to normal age-specific behaviors and is statistically deviant, in the sense that it occurs significantly more often than usual in the case of children in the same age group. For effective control of children’s inappropriate behavior, the consequences, whether positive or negative, must be immediate. Often, parents have unilateral beliefs about the causes of their children’s problematic behavior, in the sense that they believe that either they as parents are exclusively to blame, or the child is to blame.